2008
DOI: 10.1086/587187
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Acquisition of Vancomycin-Resistant Enterococci (VRE) in Roommate Contacts of Patients Colonized or Infected with VRE in a Tertiary Care Hospital

Abstract: Roommates of patients identified as colonized or infected with VRE are at substantial risk of becoming colonized, with the degree of risk increasing in older and more frail patients. VRE control programs should pay particular attention to such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 16 publications
2
18
2
Order By: Relevance
“…Risk factors for colonization and subsequent infection with VRE include having a hospital roommate colonized or infected with VRE, older age, duration of antibiotic use, specific types and numbers of antibiotics used, and the presence of a urinary catheter (320,368). Molecular and epidemiological data suggest that VRE may be transmitted to patients directly from contact with infected or colonized patients, from the hands of HCWs, or from contact with contaminated equipment or environmental surfaces (320).…”
Section: Vancomycin-resistant Enterococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors for colonization and subsequent infection with VRE include having a hospital roommate colonized or infected with VRE, older age, duration of antibiotic use, specific types and numbers of antibiotics used, and the presence of a urinary catheter (320,368). Molecular and epidemiological data suggest that VRE may be transmitted to patients directly from contact with infected or colonized patients, from the hands of HCWs, or from contact with contaminated equipment or environmental surfaces (320).…”
Section: Vancomycin-resistant Enterococcusmentioning
confidence: 99%
“…Increased mortality, longer duration of hospitalization, and increased costs are the basis of recommendations for surveillance for VRE and contact precautions recommended by the Healthcare Infection Control Practices Advisory Committee (HICPAC) (368). Also influencing these recommendations are reports of two VRE outbreaks in the early 1990s that were aborted after contact precautions were instituted, including the mandatory use of gowns and gloves by anyone in contact with infected or colonized patients (32,33,275).…”
Section: Vancomycin-resistant Enterococcusmentioning
confidence: 99%
“…Older patients and patients receiving fluoroquinolones were more likely to transmit VRE to roommates. 71 Prior guidance suggests consideration of concurrent antibiotic use, particularly antibiotics with activity against VRE, when making decisions regarding discontinuation of CP. 1 …”
Section: Duration Of Colonizationmentioning
confidence: 99%
“…Multi drug resistant or multi-resistant bacteria have predilection to effect SCI units more than general nursing wards include MRSA (methicillin resistant Staphylococcus aureus),vancomycinresistantEnterococcus(VRE),gram-negative bacilli that produce extended spectrum β lactamase(ESBL),and clostridium defficile.Roommate contacts of patients colonized or infected by any of these multi-resistant bacteria are at increased risk for acquiring those organisms [48].Of these multi-resistant organisms,MRSA is the most common; it is responsible for a large share of both hospital and community-acquired infections [49].Unlike MRSA, which could exist in almost every body organ, VRE is cultured mostly from the urine, particularly catheter-dependent patients. Although most episodes growth of VRE from urine cultures represent asymptomatic bacteremia and do not require antibiotic treatment,VRE colonization and residence in a longterm facility increase the risk for subsequent bacteremia [50].Catheter-dependent SCI patients are predisposed to develop urinary tract infection caused by ESBL-producing multi-resistant gram -negative bacilli, such as E.coli,andKlebsiella pneumoniae [51].Researchers in Malaysia reported that SCI patients with previous UTI, antibiotic usage during the past three months or history of hospitalization during past one -year were predisposed to develop infection with multi-resistant organisms [30].The frequent administration of antibiotics and relatively inadequate hygiene in SCI patients help explain the high risk of clinical infection by C.defficle.In patients with neurogenic bowel and defective sensation C.defficile associated gastrointestinal disease can remain clinically undetected until a catastrophe such as toxic megacolon or bowel perforation evolve [52].…”
Section: Infections Due To Multi-drug Resistant Organismsmentioning
confidence: 99%